Hematochezia caused by tandospirone in a patient with major depressive disorder and anxious distress: a case report - Jiang, Xingmei; Ma, Zhongrui; Li, Zhixiong; Ou, Ying; Luo, Zhenhua; Li, Zhe (Frontiers in Psychiatry, 2023)
Background: Major depressive disorder (MDD) with anxious distress is a relatively common 31 condition that is often associated with a poor treatment response. In order to enhance the effectiveness 32 of MDD treatment, 5-HT1A agonists like tandospirone are often prescribed in conjunction with 33 antidepressants. While it is known that antidepressants can increase the risk of bleeding, whether 34 tandospirone poses a similar risk remains uncertain. 35Case presentation: We presented the case of a 55-year-old Chinese woman diagnosed with MDD and 36 anxious distress. After receiving various types of antidepressants, she experienced hematochezia 37 following the administration of tandospirone, sertraline, and agomelatine. The occurrence of 38 hematochezia ceased after tandospirone was discontinued. The patient was subsequently discharged 39 with a treatment regime consisting of sertraline and agomelatine. During the 1-month follow-up, she 40 reported no hematochezia. 41 Conclusions: Tandospirone may potentially increase the risk of hematochezia in patients with MDD 42 and anxious distress. 43